Functional connectivity of the brain in older women with urgency urinary incontinence. Issue 8 (27th July 2018) - Clarkson, Becky D.; Karim, Helmet T.; Griffiths, Derek J.; Resnick, Neil M.
Abstract : Background: The brain's role in continence is critical but poorly understood. Although regions activated during bladder stimulation have been identified, little is known about the interaction between regions. In this secondary analysis we evaluate resting state and effective connectivity in older women treated for urgency urinary incontinence (UUI). Method: 54 women ≥60 years old with UUI and 10 continent women underwent fMRI scanning during provocation of urinary urgency, both before and after therapy. Response was defined by >50% reduction in leaks on bladder diary. Regions of interest (RoIs) were selected a priori: right insula, medial prefrontal cortex, and dorsal anterior cingulate cortex. Generalized psycho‐physiological interaction (gPPI) was used to calculate "effective connectivity" between RoIs during urgency. We performed a one‐way ANOVA pre‐treatment between groups (continent/responders/non‐responders), as well as a two‐way mixed ANOVA between group and time (responders/non‐responders; pre‐/post‐therapy) using false discovery rate (FDR) correction. Principal component analysis was used to assess the variance within RoIs. Exploratory voxel‐wise connectivity analyses were conducted between each RoI and the rest of the brain. Results: RoI‐RoI connectivity analysis showed connectivity differences between controls, responders, and non‐responders, although statistical significance was lost after extensive correction. Principal component analysis confirmed appropriate RoI selection. Voxel‐wise analyses showed that connectivity in responders became more like that of controls after therapy (cluster‐wise correction P < 0.05). In non‐responders, no consistent changes were seen. Conclusion: These data support the postulate that responders and non‐responders to therapy may represent different subsets of UUI, one with more of a central etiology, and one without.